Occupational Routine-Intensity and the Costs of Job Loss: Evidence from Mass Layoffs - Uwe Blien; Wolfgang Dauth; Duncan Roth (Institute of Labor Economics (IZA), 2019)
This paper analyses how differences in the degree of occupational routine-intensity affect the costs of job loss. We use worker-level data on mass layoffs in Germany between 1980 and 2010 and provide causal evidence that workers who used to be employed in more routine-intensive occupations suffer larger and more persistent earnings losses after the mass layoff. Furthermore, we are able to show that, at least initially, earnings losses are primarily due to a reduction in the number of days in employment, suggesting that routine-intensive workers face considerable frictions in the adjustment to job loss. Conditional on finding a new job, routine-intensive workers are more likely to change their occupations but end up systematically in the lower end of their new occupation's wage distribution.
Keywords: J24; J63; O33; 330; routine-replacing technological change; routine-intensity; labour market biographies; mass layoffs; Germany; difference-in-differences